ChemInform Abstract: Synthesis of New Fluorescent Building Blocks via the Microwave‐Assisted Annulation Reaction of 1, 1, 2‐Trimethyl‐1H‐benzo[e]indole with Acrylic Acid and Its Derivatives. Issue 34 (26th August 2014) - Steponaviciute, Rasa; Martynaitis, Vytas; Bieliauskas, Aurimas; Sackus, Algirdas
Abstract The title reaction gives access to benzo[e]pyrido[1.2‐α]indole derivatives, which bear reactive enaminone or enamide functionalities that can be used in several further transformations.